Different Observations and Recording Relating to Life in Hungary in 1959 - Héderváry, Claire de (1959)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Information Office Information on lawyers' income; Austrian tourists visit Budapest; the radio jamming station near the Austrian border; Sopron artisans in difficulty; Textile industry and etc.